2021
DOI: 10.3126/kumj.v19i4.49752
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Severity of Coronary Artery Disease in Diabetic and Non-diabetic Acute STEMI Patients in a Tertiary Care Centre of Nepal

Abstract: Background Patients with diabetes mellitus have a higher prevalence of atherosclerotic heart disease and a higher incidence of myocardial infarction than the general population. Definitive diagnosis and precise assessment of anatomic severity of Coronary Artery Disease requires invasive diagnostic modality like coronary angiography. Objective To study angiographic characteristics and severity involving coronary arteries in patients with acute ST segment elevation Myocardial infarction and to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Studies have indicated a strong association between diabetes mellitus and a high index of atheroma burden and extension score (Gobardhan et al, 2017;Godoy et al, 2020). Pathak and his colleagues reported no association between diabetes and the severity of coronary artery disease (Pathak et al, 2021). In the present study, we determined the association of diabetes with the localization of CAD.…”
Section: Discussionmentioning
confidence: 73%
“…Studies have indicated a strong association between diabetes mellitus and a high index of atheroma burden and extension score (Gobardhan et al, 2017;Godoy et al, 2020). Pathak and his colleagues reported no association between diabetes and the severity of coronary artery disease (Pathak et al, 2021). In the present study, we determined the association of diabetes with the localization of CAD.…”
Section: Discussionmentioning
confidence: 73%
“…Type 2 diabetes mellitus patients with poor glycaemic control are more likely to have severe atherosclerotic disease characterized by vulnerable plaques. Therefore, these patients are more likely to have acute plaque rupture and present with STEMI (44,46). Furthermore, we found that ST-segment depression on ECG was independently associated with optimal HbA1c control.…”
Section: Discussionmentioning
confidence: 75%
“…Our findings align with previous studies regarding the relationship between T2DM, endothelial dysfunction, and adverse cardiovascular outcomes[ 25 ]. Pathak et al [ 26 ] observed a significantly higher occurrence of triple vessel disease/multivessel disease in patients with a diabetes mellitus duration > 10 years compared to those with a duration < 10 years.…”
Section: Discussionmentioning
confidence: 99%